Construction of Financial Sharing Service System for New Energy Enterprises Based on Particle Swarm Optimization Algorithm - Xu, Yueran (Journal of Soft Computing and Data Mining, 2025)
Financial Shared Service (FSS) is the key to achieve enterprise strategic objectives, resolve financial problems and transform financial management methods. Facing the increasingly serious financial crisis, new energy enterprises must adopt the latest information technology to change the FSS mode. This can effectively solve many problems such as low efficiency, low quality and high cost of enterprise FSS. FSS system is a large business system with flexible structure, huge scale and needs careful design. Its progressiveness, reliability and availability need careful design. This paper proposed to use Quantum Particle Swarm Optimization (QPSO) on the basis of in-depth study of Particle Swarm Optimization (PSO). This can avoid particles falling into local optimization and improve the accuracy of PSO algorithm. By improving the inertia weight, the information exchange between individuals was increased and the population diversity was increased. The experimental results in this paper showed that when the number of tasks was 50, the time spent by PSO and QPSO at 50 iterations was 0.6s and 0.7s respectively. It took 25.0 s and 13.8 s when the number of iterations was 400. When the number of tasks was 100, PSO and QPSO spent 1.8s and 1.6s respectively when the number of iterations was 50, and 47.5s and 20.1s respectively when the number of iterations was 400. It can be seen that the speed of QPSO is higher.